2021
DOI: 10.1038/s41536-021-00172-w
|View full text |Cite
|
Sign up to set email alerts
|

Metformin accelerates zebrafish heart regeneration by inducing autophagy

Abstract: Metformin is one of the most widely used drugs for type 2 diabetes and it also exhibits cardiovascular protective activity. However, the underlying mechanism of its action is not well understood. Here, we used an adult zebrafish model of heart cryoinjury, which mimics myocardial infarction in humans, and demonstrated that autophagy was significantly induced in the injured area. Through a systematic evaluation of the multiple cell types related to cardiac regeneration, we found that metformin enhanced the autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 77 publications
1
19
0
Order By: Relevance
“…The salient findings from our current study suggested that deficiency in the autophagy initiating gene Beclin1 greatly dampened MSCs transplantation-offered benefit against post-MI myocardial injury. This result is in line with the findings from previous reports of the beneficial role of autophagy in heart regeneration (Davidson et al, 2021 ; Xie et al, 2021 ; Park et al, 2021 ). Our data revealed that MSC delivery ameliorates MI insult-induced myocardial scar fibrosis, echocardiographic, cardiomyocyte contractile and intracellular Ca 2+ dysfunction as well as mitochondrial injury accompanied by suppression of apoptosis, inflammation and autophagy defect.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The salient findings from our current study suggested that deficiency in the autophagy initiating gene Beclin1 greatly dampened MSCs transplantation-offered benefit against post-MI myocardial injury. This result is in line with the findings from previous reports of the beneficial role of autophagy in heart regeneration (Davidson et al, 2021 ; Xie et al, 2021 ; Park et al, 2021 ). Our data revealed that MSC delivery ameliorates MI insult-induced myocardial scar fibrosis, echocardiographic, cardiomyocyte contractile and intracellular Ca 2+ dysfunction as well as mitochondrial injury accompanied by suppression of apoptosis, inflammation and autophagy defect.…”
Section: Discussionsupporting
confidence: 93%
“…Up-to-date, a number of scenarios have been put forward for MSCs-offered cardioprotection including anti-apoptosis and pro-angiogenesis (de Freitas et al, 2021 ). More recently, autophagy was shown to positively correlate with metformin-induced heart regeneration in zebrafish and suggests the value of this diabetic drug for amelioration of MI injury (Xie et al, 2021 ). In addition, inhibition of mammalian target of rapamycin (mTOR) using HY-1685 may also rejuvenate senile human cardiac stem cells through modulating autophagy to improve human cardiac stem cell cell-based myocardial regeneration (Park et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we subjected TNNT2-FUCCI hiPSC-derived CMs to a library of compounds regulating autophagy. Autophagy has been implicated in heart regeneration ( 43 ) and exerts numerous roles in myocardial stress responses ( 44 ). Autophagy reduces cellular stress caused by reactive oxygen species, which in turn plays a role in cardiomyocyte cell cycle exit ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the activation of autophagy was also involved in the anti-inflammatory effects of resveratrol in TNF-α-treated HCAECs [199]. Furthermore, autophagy was found to be upregulated during zebrafish heart regeneration and was positively correlated with the metformin-mediated cardiac regeneration acceleration in zebrafish, including epicardial, endocardial, and vascular endothelial regeneration [200]. Moreover, recent studies show that in aged EC compartments, autophagic activities are compromised [89].…”
Section: Coronary Endothelial Autophagy In Other Heart Diseasesmentioning
confidence: 95%